Penguatan Kapasitas Manajerial BUMDes Bangun Mandiri Melalui Optimalisasi UMKM Produk Lokal untuk Peningkatan Ekonomi Desa Bekiung - Kholik, Kholilul; Taufik, Ahmad; Hajar, Siti; Arma, Nur Ambia (Nawadeepa: Jurnal Pengabdian Masyarakat, 2025)
This Community Service Program (PKM) aims to strengthen the managerial capacity of the Village-Owned Enterprise (BUMDes) "Bangun Mandiri" in Bekiung Village through optimization of micro, small, and medium enterprises (UMKM) based on local products to encourage the improvement of the village economy. The methods used in this activity include need assessment for mapping local problems and potentials, a participatory approach in community involvement, training to strengthen BUMDes managerial capacity, and mentoring for local business incubation based on village potential. The results of the activity showed a significant increase in the understanding and managerial skills of BUMDes administrators, as well as the development of local MSME capacity in terms of legality, branding, and digital marketing. This activity proves that the synergy between strengthening village institutions and empowering the community economy based on local products can be an effective strategy in encouraging the independence and sustainability of the village economy.